Design of Food Product Using Quality Function Deployment in Food Industry - Purwanto, Agus (AGUSPATI Research Institute, 2020)
Decrease profits, decreased sales turnover and the customer complaint and the number of brands that compete with each other in the snack food beverage market, encourage PT. X to find out the attributes desired by consumers, PT. X conducted research on the development of snack products using the QFD (Quality Function Deployment) method. The main objective to be achieved in this research is to provide a Product Design proposal, process planning and production planning to improve the competitiveness of PT. X by using the 4-phase Quality Function Deployment (QFD) tool. This study used respondents of 130 distributors who collaborated with PT. X. After the data processing the questionnaire was continued by compiling the four Quality Function Deployment matrices generated from the house of quality matrix namely Main Raw Materials in the form of Corn, direct prizes in the form of cash Rp 8,000 per carton, seasoning composition by 10 persen, moisture content by 3 persen, carton size 42x23x22cm, packaging size 14x10cm, OPP 30 packaging material, orange packaging color, cartoon packaging images, yellow food color, round food dimensions, food age 12 mth, Number of Contents per carton 40 pcs. The critical part that results from the preparation of the design deployment matrix are snack weight. Amount of water content, number of spices, type of base, weight of the base. The selected process stages that are generated from the process planning matrix are Mixing of Raw Materials, Adding Dyes, Making Base, Reducing Moisture Content, Add Seasonings. Production stages that are produced from the production planning matrix are procedures, operator training, Mistake Proofing, Failure Prevention Action Required, Operator Instruction, Work Analysis, Supplier Conference, Supplier Agreement, Maintenance Instruction, Gauge Design, Machine Qualification, Gauge Requirements. To produce quality products and in accordance with customer requirements, PT.X must focus on the requirements resulting from the preparation of the four Quality Function Deployment matrices.